2017
DOI: 10.1097/inf.0000000000001505
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Response to First-line Efavirenz- or Nevirapine-based Antiretroviral Therapy in HIV-infected African Children

Abstract: Background:Poorer virologic response to nevirapine-versus efavirenzbased antiretroviral therapy (ART) has been reported in adult systematic reviews and pediatric studies. Methods: We compared drug discontinuation and viral load (VL) response in ART-naïve Ugandan/Zimbabwean children ≥3 years of age initiating ART with clinician-chosen nevirapine versus efavirenz in the ARROW trial. Predictors of suppression <80, <400 and <1000 copies/mL at 36, 48 and 144 weeks were identified using multivariable logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
3
2
1
Order By: Relevance
“…Similar results were reported from the ARROW trial, where 80% of a Ugandan/ Zimbabwean paediatric cohort had achieved VL < 80 and 90.5% <400 copies/mL after 36 weeks of efavirenz-based therapy. 30 We found that PDR and high baseline VL predicted ADR after 6 months of NNRTI-based treatment, which is in line with previous findings in ART-naïve Ugandan children. 14 In other short-and long-term follow-ups, both young children 16,30,31 and adolescents 30 showed that NRTI resistance increased markedly from 2% to 11%, mainly due to the emergence of M184V.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results were reported from the ARROW trial, where 80% of a Ugandan/ Zimbabwean paediatric cohort had achieved VL < 80 and 90.5% <400 copies/mL after 36 weeks of efavirenz-based therapy. 30 We found that PDR and high baseline VL predicted ADR after 6 months of NNRTI-based treatment, which is in line with previous findings in ART-naïve Ugandan children. 14 In other short-and long-term follow-ups, both young children 16,30,31 and adolescents 30 showed that NRTI resistance increased markedly from 2% to 11%, mainly due to the emergence of M184V.…”
Section: Discussionsupporting
confidence: 92%
“…30 We found that PDR and high baseline VL predicted ADR after 6 months of NNRTI-based treatment, which is in line with previous findings in ART-naïve Ugandan children. 14 In other short-and long-term follow-ups, both young children 16,30,31 and adolescents 30 showed that NRTI resistance increased markedly from 2% to 11%, mainly due to the emergence of M184V. This DRM is commonly selected under lamivudine pressure but is known to reduce viral fitness and may benefit net antiviral activity, even during lamivudine monotherapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most recent WHO guidelines recommend the use of LPV/r -based ART in children under 3 years of age and efavirenz-based ART in those above 3 years of age, with NVP-based ART as an alternate regimen[ 6 ]. However, due to delayed uptake and availability, NVP use in Africa remains high[ 30 , 31 ]. Thus it remains important to ensure the proper use of antimalarials in the context of NVP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In another study to assess the virologic response to first-line ART based on EFV or NVP in 836 children aged 3 years or more in Africa (Uganda and Zimbabwe), 445 (53%) children received EFV and 391 (47%) received NVP. The pre- mature viral inhibition was more frequent in the EFV recipients during the 36 -48 weeks of treatment (33). In a study conducted in Kampala, Uganda, which compared the therapeutic effect of two regimens based on NVP or LPV/r, 329 infants or children receiving NVP-based ART regimen experienced a clear risk of virologic failure and death more than LPV/r recipients (9.1 times) (34).…”
Section: Discussionmentioning
confidence: 99%